Safety, pharmacokinetics and pharmacodynamics of GLPG0974, a potent and selective FFA2 antagonist, in healthy male subjects - Namour, Florence; Galien, René; Van Kaem, Tim; Van der Aa, Annegret; Vanhoutte, Frédéric; Beetens, Johan; Klooster, Gerben (British journal of clinical pharmacology, 2016)
Aims Free fatty acids (FFA) can act as direct signalling molecules through activation of several membrane‐bound G‐protein coupled receptors. The FFA2 receptor (known as GPR43) is activated by short chain fatty acids (SCFA) such as acetate and has been shown to play a major role in SCFA‐induced neutrophil activation and migration and to contribute in the development and control of inflammation. GLPG0974 is a potent and selective antagonist of the human FFA2. The main objectives of the two phase 1 trials were to characterize the safety, tolerability, pharmacokinetics and pharmacodynamics of GLPG0974. Methods Two consecutive randomized, double‐blind, placebo‐controlled, single centre trials in healthy subjects were performed. In the first, GLPG0974 was administered as single doses up to 250 mg and in the second, multiple daily doses up to 400 mg for 14 days were evaluated. Non‐compartmental analysis was used to determine GLPG0974 pharmacokinetics while target engagement was investigated through the inhibition of neutrophils in acetate‐simulated whole blood samples using surface expression of CD11b activated epitope as a marker of neutrophil activation. Results The investigation of safety/tolerability and pharmacokinetics in the early development phase showed that GLPG0974 was safe and well tolerated up to a daily dose of 400 mg. GLPG0974 showed good and dose proportional exposure up to 400 mg daily as well as a substantial and sustained inhibition of acetate‐stimulated neutrophil activation. Conclusion Based on these results, a proof‐of‐concept study was initiated to evaluate the safety, tolerability and efficacy of GLPG0974 in patients with mild to moderate ulcerative colitis.